Analyzing the Effect of Dual Role Conflict and Work Stress on Female Employee Performance Using SEM in Bandung Regency - Utami, Intan Cahya; Sary, Fetty Poerwita (Jurnal Locus Penelitian dan Pengabdian, 2025)
Human resource management plays a crucial role in organizational success, with employees expected to contribute effectively to company goals. This study examines the impact of dual role conflict and work stress on the performance of female employees in Bandung Regency. These factors are particularly relevant for women, who often face the challenge of balancing work responsibilities with family duties. The study uses a quantitative approach with causal descriptive research, involving 140 married female employees from the formal sector. Data was collected through questionnaires and analyzed using Structural Equation Modeling (SEM). The results reveal that both dual role conflict and work stress significantly negatively affect female employees' performance, explaining 41.7% of performance variations. The study concludes that organizations should implement policies such as work flexibility, stress management programs, and supportive environments to help female employees manage these challenges. These strategies can improve productivity and job satisfaction, thereby enhancing overall organizational performance. Additionally, further research is recommended to explore other influencing factors such as social support and leadership styles to provide a more comprehensive understanding of female employees' work-life dynamics.